Verbal and Non-Verbal Marketing Strategies of Vegetable Vendors During Market Day in Aborlan, Public Market - Tulukan, Joshua Jay; Saldevia, Gladys Joy; Palermo, Dexter; Tilos, Daisy; Villaran, Jeffrey; Reyes, Princess Delos; Sebido, Maria Asela; Loreño, Dustin (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The study was conducted to evaluate both the verbal and non-verbal marketing strategies employed by vegetable vendors during Market Day at Aborlan Public Market. The study also aimed to assess the advantages and effects of these strategies on the business, as well as to identify the challenges encountered in vegetable marketing. Employing a descriptive method, the respondents consisted of vegetable vendors present at Aborlan Public Market during Market Day, selected based on their availability for interviews. The study revealed that vegetable vendors derived benefits from the implementation of their chosen verbal and non-verbal marketing strategies. These strategies proved effective in attracting buyers, promoting products, building relationships with customers, and fostering customer retention. Furthermore, the utilization of these strategies enabled vegetable vendors to enhance their sales performance.